Diagnostic Dilemma of Hemolytic Anemia: A Reveal Secondary to Gastric Adenocarcinoma - Gautam, Prerana; Singh, Ishwor Man; Limbu, Bimas Payangu; Vaidya, Monasha; Rai, Ujwal (Medical Journal of Eastern Nepal, 2023)
Here is a case report of a 62-year-old female who presented to our hospital with complaints of abdominal pain, unresolving severe anemia, bleeding per rectum with history of multiple blood transfusions at outside hospital. On initial investigations, the findings directed towards case of hemolytic anemia. The cause of hemolytic anemia was still unknown even after extensive clinical and laboratory investigations. Bone marrow biopsy was done, which revealed metastatic adenocarcinoma and diagnosis of cancer-related microangiopathic haemolytic anaemia (CR-MAHA) was established. Endoscopic biopsy was done from gastric growth which revealed gastric adenocarcinoma and final diagnosis of microangiopathic hemolytic anemia secondary to gastric adenocarcinoma was made.The patient’s haematological parameters improved with chemotherapy directed against the gastric adenocarcinoma. Our case supports the findings of various literature which indicates that the gastric cancer-associated MAHA responds well to the treatment with chemotherapy for primary carcinoma.